2014
DOI: 10.4067/s0717-95022014000300044
|View full text |Cite
|
Sign up to set email alerts
|

Facial Soft Tissue in Subjects with Class II and Class III Facial Deformities: Preliminary Results

Abstract: SUMMARY:Class II and class III skeletal anomalies require treatments that are both esthetic and functional, so the purpose of this investigation was to study the relationship between facial soft and hard tissues of patients with class II and class III deformities in the lower third of the face. A descriptive study was designed which included class II subjects with a SNB angle less than 78º and class III with a SNA angle less than 80º. The soft tissue width was analyzed in relation to the Pg point, A point, B p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
0
1
1
Order By: Relevance
“…The nasolabial angle (lower angle that relates the nasal base to the labial superior) presents a norm from 90º to 110º, but in our sample it showed a value less than 81º. Previous studies by Olate et al (2014aOlate et al ( , 2014b showed this same nasolabial angle in Class III subjects with values of 100º, which stayed within the norm and creates confusion when comparing it to the present results.…”
Section: Discussioncontrasting
confidence: 51%
“…The nasolabial angle (lower angle that relates the nasal base to the labial superior) presents a norm from 90º to 110º, but in our sample it showed a value less than 81º. Previous studies by Olate et al (2014aOlate et al ( , 2014b showed this same nasolabial angle in Class III subjects with values of 100º, which stayed within the norm and creates confusion when comparing it to the present results.…”
Section: Discussioncontrasting
confidence: 51%
“…El estudio de imágenes tridimensionales es constantemente utilizado en el diagnóstico y planificación quirúrgica, transformándolas en elementos básicos para el estudio morfológico (Olate et al, 2012(Olate et al, , 2014a. Ventajas importantes de este sistema para el análisis en morfología facial se asocian a la ausencia de modificaciones de la muestra (no existe necesidad de interrupción en muestras anatómicas) y al hecho de presentar una muestra anatómi-ca integral donde se pueden asociar otras variables anató-micas del sector estudiado (Li et al, 2006).…”
Section: Introductionunclassified